Study of bullying behavior and its risk factors among primary school students in Sohag Governorate - Nabiel Metwaly; Islam Shaaban; Marwa S.G Ali (Wolters Kluwer Medknow Publications, 2022)
Background and aim Bullying is one of the most serious problems that children face in the education system. Several other studies have found that bullying represents a standard problem in schools worldwide. This study aims to assess the incidence of school bullying as well as its suspected risk factors among primary school students. Patients and methods The study included 280 primary school students (146 males and 134 females) aged from 10 to 12 years old in the first stage of the study for screening for bullying behavior. A self-administered questionnaire was used to collect data about the bullying behavior among the selected students. The questionnaire was adopted from the validated Arabic version of Bullying Behavior Scale for children and adolescents. Results The incidence of significant bullying among the included students was found to be 12.5%, with males showing higher degrees of bullying. There was a significant association between involvement of the student in the bullying behavior and the risk factors such as student exposure to frequent punishment and negative attitude by the teacher, lack of acceptance from colleagues, and exposure to previous bullying. Conclusion Male students in primary schools showing higher degrees of bullying with significant association were found between bullying behavior and its risk factors.